Clinicopathological study of benign breast diseases a study of 50 cases - Chaudhary, Manish; Bhat, Purvesh; Wankhede, Vedant; Aagja, Jigar; Rathva, Dhaval; Ahir, Tushar (International Surgery Journal, 2021)
Background: Benign breast diseases are a neglected entity in developing countries despite the fact that they involved in the majority of breast complaints. Benign breast disorders can be defined as any non-malignant breast condition and involved wide range of clinical and pathological disorders. Breast diseases present as swellings. It is a symptom/sign for a different lesion varying from developmental abnormality, inflammatory lesions, epithelial and stromal proliferation to malignancy. Patients were studied on the basis of i.e., clinically, and histopathological ultrasound has done. Our purpose of study is to document various benign Brest diseases to study different mode of presentations of diseases and correlation of clinical and pathological diagnosis Methods: The given study was a prospective and observational study, undertaken in the department of general surgery, govt. medical college Surat, during the study period of March 2018 to September 2019.All the female and male patients with breast related disease were included in this study. Female patients with biopsy proven malignancy were excluded from the study. Results: The study comprised of 50 patients with benign breast diseases; the most common is Fibro adenoma which formed 68% then fibrocystic diseases 20%. With most common age group involved in our study is 21-30 years. Conclusions: Benign breast diseases are more common but ignored entity though it carries majority of complaints and occur mainly in young women less than 30 years of age and were mostly fibro adenoma and fibrocystic change.